Urgensi Kajian Tarikh al-Tasyri’ dalam Formulasi Hukum Islam Kontemporer - Salwa Husni Aprilia Pasaribu; Nur Azizah Shazrina; Rizky Ananda Marpaung; Ali Yanda Safaruddin Tanjung; Arman Alfiansyah Hasibuan (Albayan Journal of Islam and Muslim Societies, 2025)
The study of Tarikh al-Tasyri‘ is a discipline that traces the formation of Islamic law from the prophetic era to the modern age, providing an essential historical framework for formulating contemporary Islamic legal rulings that remain adaptive while rooted in the tradition of the Shari‘ah. This research employs a qualitative, library-based approach to explore the development of Islamic legislation through key phases, beginning with the revelation of the Qur’an, the practices of the Companions, the formation of legal schools, and the transformation of law in the modern nation-state era. The findings indicate that Islamic law possesses dynamic, historical, and contextual characteristics, making an understanding of its historical trajectory crucial for interpreting the law accurately within the context of rapid social change. The integration of Tarikh al-Tasyri‘, maqasid al-shari‘ah, and contemporary ijtihad methodologies forms the epistemological foundation for constructing modern Islamic law that is not only normative but also relevant and responsive to present-day challenges. The novelty of this study lies in utilizing the history of legislation not merely as a descriptive record but as an active epistemological source for formulating contemporary approaches to Islamic legal thought.